Effectiveness of Interactive Learning Media Development Based on Articulate Storyline 3 in Elementary School Education - Adawiyah, Elok Robiatul; Winarno, Ahmad; Onia, Saifaldin Idris (EDUCARE: Journal of Primary Education Published by Faculty of Tarbiyah and Teacher Training, Kiai Haji Achmad Siddiq State Islamic University of Jember, East Java, Indonesia, 2024)
The development of learning media in the form of interactive media involving animations, quizzes, and videos facilitates better understanding of learning material through two-way communication between the media and students, making the material more concrete and easier to comprehend. This study aims to develop an interactive learning media product based on Articulate Storyline 3 for use in elementary schools and to describe the feasibility of this media in such settings. The method used is Research and Development (R&D) with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. This research contributes to the development of interactive learning media using Articulate Storyline in private elementary schools, improving student learning outcomes and enhancing the overall learning process at the elementary level. The results show that interactive media based on Articulate Storyline 3 effectively enhances student understanding, particularly in abstract topics such as magnetism. Its features promote active learning, improve academic performance, and support various learning styles. Developed using the ADDIE model, the media fosters an inclusive and engaging learning environment. However, its success depends on teacher readiness and available infrastructure. Overall, this media offers an innovative approach to enrich primary education. This study contributes to the development of interactive learning media based on Articulate Storyline 3, which is effective in enhancing students' understanding, especially in abstract topics like magnetism. By supporting active learning and various learning styles, this media offers an innovative approach to enrich the learning experience in primary education.